Neurologic complications of influenza A(H1N1)pdm09 surveillance in 6 pediatric hospitals - Khandaker, G.; Zurynski, Y.; Buttery, J.; Marshall, H.; Richmond, P.; Dale, R.; Royle, J.; Gold, M.; Snelling, Thomas; Whitehead, B.; Jones, C.; Heron, L.; et al. (Lippincott Williams & Wilkins, 2012)
Objective: We sought to determine the range and extent of neurologic complications due to pandemic influenza A (H1N1) 2009 infection (pH1N1'09) in children hospitalized with influenza. Methods: Active hospital-based surveillance in 6 Australian tertiary pediatric referral centers between June 1 and September 30, 2009, for children aged < 15 years with laboratoryconfirmed pH1N1'09. Results: A total of 506 children with pH1N1'09 were hospitalized, of whom 49 (9.7%) had neurologic complications; median age 4.8 years (range 0.5-12.6 years) compared with 3.7 years (0.01-14.9 years) in those without complications. Approximately one-half (55.1%) of the children with neurologic complications had preexisting medical conditions, and 42.8% had preexisting neurologic conditions. On presentation, only 36.7% had the triad of cough, fever, and coryza/ runny nose, whereas 38.7% had only 1 or no respiratory symptoms. Seizure was the most common neurologic complication (7.5%). Others included encephalitis/encephalopathy (1.4%), confusion/disorientation (1.0%), loss of consciousness (1.0%), and paralysis/Guillain-Barre' syndrome (0.4%). A total of 30.6% needed intensive care unit (ICU) admission, 24.5% required mechanical ventilation, and 2 (4.1%) died. The mean length of stay in hospital was 6.5 days (median 3 days) and mean ICU stay was 4.4 days (median 1.5 days). Conclusions: Neurologic complications are relatively common among children admitted with influenza, and can be life-threatening. The lack of specific treatment for influenza-related neurologic complications underlines the importance of early diagnosis, use of antivirals, and universal influenza vaccination in children. Clinicians should consider influenza in children with neurologic symptoms even with a paucity of respiratory symptoms. © 2012 by AAN Enterprises, Inc.